2021
DOI: 10.1071/bt20102
|View full text |Cite
|
Sign up to set email alerts
|

Differences in emergence and flowering in wild, re-introduced and translocated populations of an endangered terrestrial orchid and the influences of climate and orchid mycorrhizal abundance

Abstract: Re-introduction and translocation are conservation strategies often employed to circumvent declining wild orchid populations but their efficacy as conservation strategies is widely debated. The aim of this study was to investigate the long-term efficacy of re-introduction and translocation strategies for an endangered orchid as its climate changed. Vital rates of the wild, re-introduced and translocated populations of an endangered terrestrial orchid Caladenia amoena were compared from 2008 to 2019. Emergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It has been shown that understanding the mycorrhizal diversity and density in the reintroduction site is also key to successful population establishment [ 35 ]. Testing sites suitable for reintroduction/translocation of rare orchids with symbiotic seedlings offer opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that understanding the mycorrhizal diversity and density in the reintroduction site is also key to successful population establishment [ 35 ]. Testing sites suitable for reintroduction/translocation of rare orchids with symbiotic seedlings offer opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Putative mycorrhizal fungi from protocorms [ 36 ] or seedlings [ 37 , 38 ] serve as reliable symbionts for seed germination. In some cases, the orchid seeds can only be germinated by a specific lineage of the mycorrhizal fungus from protocorms [ 35 ]. The current study used fungi available from plants at different growth phases and found that Tulsanella OTU from mature phase D. praetermissa was a germination-compatible fungus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of natural or translocated populations of orchids have often assessed habitat suitability at the population level and for suitability of adult persistence (Janes et al 2010;Duncan and Moloney 2018;Janissen et al 2021), or if comparing microsites, examined the persistence of flowering individuals (Moisan and Pellerin 2013), rather than seedlings. Investigation of microsites suitable for germination of terrestrial orchids (regenerative niche) has been undertaken using seed-burial trials, which is when seed is put in packets and buried near plants or across transects in existing populations (Rasmussen et al 2015).…”
mentioning
confidence: 99%
“…Similarly, changes in rainfall patterns between years could see orchids germinate that may not survive (Jersáková and Malinová 2007). In the case of many threatened species, sites may be degraded, within the urban landscape (Duncan and Moloney 2018;Janissen et al 2021) and unrepresentative of the broader habitat requirements of the species. To optimise conservation translocation plantings and funding to the greatest effect, and ensure successful recruitment and sustainable populations, we need to know both the sites that are suitable for adult plants and the sites that are suitable for recruitment, and where these intersect.…”
mentioning
confidence: 99%